Ethical management and business theology of modern banjar kiyai analysis of business management of kiyai followers of Guru Sakumpul Martapura and pesantren managers in South Kalimantan - Abdul Sani; Ahmad Syazali; Abdul Hakim; H. Ibnu Arabi (Sean Institute, 2024)
The behavior of Banjar kiyai or ulama in South Kalimantan, especially Pondok Pesantre caregivers, is trending and interesting to explore and study in depth, especially in the sense of modernity of thinking,